2004
DOI: 10.1042/cs20030182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with arachidonic acid on platelet and renal function in patients with cirrhosis

Abstract: Advanced cirrhosis is associated with reduced platelet function and altered renal function and sodium handling. Arachidonic acid (AA) metabolites contribute to platelet aggregation and to maintain the response to diuretics in advanced cirrhosis. In the present study, we tested the effects of a dietary supplementation for 8 weeks with a triacylglycerol (triglyceride) enriched in AA (ARASCO; 4 g/day) or oleic acid (OA) on plasma and membrane fatty acid composition, platelet aggregation and renal prostaglandin (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…In vivo PG production by dietary supplements with pure ARA (e.g., 6 g/day for 2-3 weeks in humans) can be slightly increased [19]. These studies suggest that eicosanoid formation is not promptly influenced by ARA dietary intake, at least within the range of traditional human diets [20, 21]. However, it has been shown that very high amounts of fish oil may decrease PG formation with consequent weak anti-inflammatory and analgesic effects [22].…”
Section: Effects Of Epa and Dha On Oxygenated Eicosanoid Biosynthementioning
confidence: 99%
“…In vivo PG production by dietary supplements with pure ARA (e.g., 6 g/day for 2-3 weeks in humans) can be slightly increased [19]. These studies suggest that eicosanoid formation is not promptly influenced by ARA dietary intake, at least within the range of traditional human diets [20, 21]. However, it has been shown that very high amounts of fish oil may decrease PG formation with consequent weak anti-inflammatory and analgesic effects [22].…”
Section: Effects Of Epa and Dha On Oxygenated Eicosanoid Biosynthementioning
confidence: 99%
“…In humans and in animal models of chronic liver disease and cirrhosis, there is a clear hypoaggregability, as demonstrated with in vitro aggregation tests (the gold standard) 5, 61, 65–74 and with flowcytometric analysis of stimulation dependent antigens (e.g. P‐selectin) 70 .…”
Section: Platelet Functionmentioning
confidence: 99%
“…9, 10 Arachidonic acid and its lipid metabolites have important roles in human inflammatory diseases, 11, 12, 13 which suggests that 12/15-LO can be a pathogenic player that mediates inflammatory responses in vivo . 12/15-LO is widely expressed in the CNS, 14, 15 and has been demonstrated to be involved in the pathogenesis of various neurological diseases.…”
mentioning
confidence: 99%